Impact of educational intervention on hypertension management by primary care physician (PUMP trial). - Ashraf, Tariq; Kanwal Fatima; Nadeem, Asif; Masood, Arslan; Mahmood Ul Hassan; Raza, Haseeb; M Abdur Rauf; Jalal Ud Din; Shah, Saeedullah; Kha, Fayza Khan; et al. (International Journal of Endorsing Health Science Research, 2021)
Background: To date, no optimal way of organizing and delivering care to hypertensive patients at the primary carer level has been identified, due to which a significant number of patients fail to meet the treatment goals. The current study aims to observe hypertension educational intervention's effect on general physicians (GPs) to indirectly improve blood pressure control and patient outcomes. Methodology: In this randomized control trial, GPs will be divided into 2 groups and both groups will be asked to fill hypertension awareness questionnaire at baseline and, after randomization. GPs of the group I will receive (1 day) face-to-face education with structured educational material on hypertension management strategies. GPs of group II will receive the print version of educational material (structured educational material) on strategies of structured hypertension management. Both groups of GPs will recruit 10 (5 newly diagnosed + 5 already diagnosed patients) from the study site. The patient will be asked to fill hypertension awareness questionnaire at baseline and share a 12-hour blood pressure measurement. GPs and patients will be reassessed after 3 months of intervention. Discussion: The purpose of designing this study is to observe the effect of hypertension educational intervention for general physicians to improve blood pressure control and patient outcomes indirectly. Results of this study may provide a basis for developing a hypertension educational program targeted at general physicians. Trial registration: The trial was registered with ClinicalTrials.gov NCT05038774.